Tracing the journey of Thattai Bhatia community through their culinary identity - Navreet Kaur Rana (BMC, 2021)
Abstract The paper acknowledges the remarkable contribution of cookbooks which have always played an instrumental role in researching the history of any community. However, it brings to light the fact that there are several reasons like migration, small size of the community or the nomadic lifestyles when the culinary regime of the community could not be documented. In such cases, the everyday food choices of an ethnic community can lead us to tracing its origin and journey. The paper, thus, argues that in situations where there is paucity of literature documenting the culinary system or foodways, culinary identity of the community can become an effective method to trace the history of the community. The same is proved with the help of a case study of the Thattai Bhatia community. Thattai Bhatia is a small diaspora largely settled in the Persian Gulf, originally migrated from Rajasthan in India and later from Thatta in Sindh, Pakistan. The research reveals the reasons behind their distinct foodways such as abstinence from consuming liquor, meat, garlic and onion in particular, despite their intermingling with different ethnicities due to migration. The paper draws evidences from their regular foodways and traverses backwards to trace their origins, their history and the reasons that have shaped their contemporary food choices. With limited availability of literature, the author had to depend on the information provided during interviews by some of the community members about their food practices. All the findings are substantiated with references from the historical literature available.